Sex-specific association between inflammation and endothelial function relevant gene and vulnerable carotid plaque - Li, Jie; Zhang, Ping; Yi, Xingyang; Luo, Hua; Yu, Ming; Chen, Hong; Wang, Chun (Frontiers in Physiology, 2022)
Objectives: We aimed to explore sex-specific association between genes involved in inflammation and endothelial function and vulnerable carotid plaque, a subclinical precursor of ischemic stroke. Methods: Carotid plaque and plaque phenotype were assessed by carotid ultrasound in high-risk participants for stroke drawn from a multicenter, cross-sectional survey in southwestern China. We examined 18 single nucleotide polymorphisms (SNPs) in 10 genes related to inflammation and endothelial function. Sex differences in the genotype of the candidate SNPs and risk of vulnerable carotid plaques were assessed. Interaction tests were performed to identify the SNPs that might modify the association between the sex and vulnerable plaques. For SNPs with suggestive evidence for interaction with sex (p for interaction<0.05), stratification analysis by sex was performed to evaluate the sex-specific association between the SNP and vulnerable plaques. Results: 2644 high-risk individuals were enrolled, comprising 1202 (45.5%) men and 1442 (54.5%) women. Vulnerable carotid plaques were detected in 425 (16.1%) participants. Among candidate SNPs, the genotype frequencies of 5 SNPs (TNFSF4 rs11811788, TNFSF4 rs1234313, IL6R rs4845625, VCAM1 rs2392221, and ITGA2 rs1991013) were significantly different between sex (all p<0.05). Univariable and multivariable analyses suggested that male individuals had a significantly higher prevalence of vulnerable carotid plaques (20.0% vs. 12.8%, adjusted OR 1.72, 95% CI 1.12-2.66, p=0.014), while none of the candidate SNPs was significantly associated with vulnerable plaques (all p>0.05). Interaction tests found the association between sex and vulnerable plaques is affected by the genotype of IL6R rs4845625 (p for interaction=0.031). Stratification analysis revealed a strong association between IL6R rs4845625 and vulnerable carotid plaque in man (dominant model TT vs. CT+CC: adjusted OR 1.52, 95%CI 1.12-2.07, p=0.007; codominant model TT vs. CC: adjusted OR 1.50, 95%CI 1.00-2.25, p=0.048) but not in women (p>0.05 in all genetic models). Conclusion: The rs4845625 polymorphism in IL6R has sex-specific effects on vulnerable carotid plaque in Chinese Han high-risk individuals for stroke. Our findings provide a plausible genetic basis underlying the sex difference in carotid plaque vulnerability.